Occurence and biological aspects of the clitoria tree psyllid in Brazil (Scientia Agricola, 2005)
Clitoria fairchildiana (Howard) is a tree largely distributed in Brazil, used for urban arborization. In April 2001, the psyllid Euphalerus clitoriae Burckhardt & Guajará was reported on this plant in the metropolitan areas of Recife, PE, Brazil. This report records the occurrence of E. clitoriae and studies some of its biological aspects in this area. With this purpose, C. fairchildiana leaves were sampled weekly, and E. clitoriae nymphs as well as Aprostocetus sp. larvae and nymphs were collected and counted. The E. clitoriae population ranged from 2 to 90 nymphs per leaflet. The Aprostocetus sp. percentage of parasitism ranged from 3 to 24%. The frequency curve for pygidium width ranged from 120 to 140; 200 to 240; 300 to 380; 460 to 580, and 720 to 820 mm for the first, second, third, fourth, and fifth instars, respectively. The incubation period for E. clitoriae eggs lasted 7.6 days. The nymphal stage lasted 5.7; 4.5; 4.8; 5.0, and 6.1 days for the first, second, third, fourth, and fifth instars, respectively. Development time from egg to adult was 33.7 days. Female longevity 8.6 days, with a daily fecundity of 118 eggs. The total viability of the immature stage was 74%, and the sex ratio was 0.5.